2015
DOI: 10.5812/aapm.30062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous Acetaminophen (Paracetamol) on Hemodynamic Parameters Following Endotracheal Tube Intubation and Postoperative Pain in Caesarian Section Surgeries

Abstract: Background:Use of analgesics, especially opioids, before delivery during cesarean section for preventing hemodynamic changes after endotracheal intubation and postoperative analgesia is limited due to their adverse effects on the neonate.Objectives:The aim of this study was to investigate the effect of intravenous acetaminophen (paracetamol) in blunting hemodynamic responses to endotracheal intubation and postoperative pain in parturient undergoing cesarean section by general anesthesia.Patients and Methods:Ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…A placebo controlled trial conducted by Soltani G et al on these patients showed that acetaminophen reduced tachycardia in response to endotracheal intubation when used before induction but has no effect on rise in blood pressure. 10 Our trial partially agrees with this study as it shows no significant blunting in rise of heart rate as well as blood pressure.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A placebo controlled trial conducted by Soltani G et al on these patients showed that acetaminophen reduced tachycardia in response to endotracheal intubation when used before induction but has no effect on rise in blood pressure. 10 Our trial partially agrees with this study as it shows no significant blunting in rise of heart rate as well as blood pressure.…”
Section: Discussionsupporting
confidence: 90%
“…7,8 Studies conducted in the past to assess the efficacy of acetaminophen in attenuating the DOI: 10.29309/TPMJ/2020.27. 2.3921 hemodynamic presser response 9,10 found it to be efficacious. Acetaminophen has also been compared with local anesthetic agents like lidocaine.…”
Section: Introductionmentioning
confidence: 99%
“…Though its role in pre-emptive approach to management of postoperative pain has been adequately studied by various authors [12][13][14], there is paucity of work on utilization of paracetamol as an intrapartum analgesic drug. Thus, it appeared apposite to design a randomized trial to investigate the proposed use of acetaminophen.…”
Section: Introductionmentioning
confidence: 99%
“…paracetamol during intrapartum period. [9][10][11][12][13][14][15][16][17][18] Elbohoty and colleagues 9 showed that use of i.v. paracetamol, was as effective as pethidine for intrapartum analgesia during the first stage of labour.…”
Section: Discussionmentioning
confidence: 99%
“…morphine, 14,15 or with saline during Caesarean section under general anaesthesia. [16][17][18] To the best of our knowledge, no study has compared the role of i.v. paracetamol as an adjunct analgesic agent, to the well established labour analgesia regimes.…”
mentioning
confidence: 99%